Crystal structure of tripartite-type ABC transporter MacB from Acinetobacter baumannii - Okada, Ui; Yamashita, Eiki; Neuberger, Arthur; Morimoto, Mayu; van Veen, Hendrik W.; Murakami, Satoshi (Nature communications, 2017)
The MacA–MacB–TolC tripartite complex is a transmembrane machine that spans both plasma membrane and outer membrane and actively extrudes substrates, including macrolide antibiotics, virulence factors, peptides and cell envelope precursors. These transport activities are driven by the ATPase MacB, a member of the ATP-binding cassette (ABC) superfamily. Here, we present the crystal structure of MacB at 3.4-Å resolution. MacB forms a dimer in which each protomer contains a nucleotide-binding domain and four transmembrane helices that protrude in the periplasm into a binding domain for interaction with the membrane fusion protein MacA. MacB represents an ABC transporter in pathogenic microorganisms with unique structural features. The tripartite multidrug efflux pump MacA-MacB-TolC in Gram-negative bacterial pathogens is driven by the ATPase MacB, which belongs to the ATP-binding cassette (ABC) superfamily. Here the authors present the 3.4 Å resolution crystal structure of MacB, and compare it with other known ABC transporter structures.